'Green' strategies and approaches. A contribution from the off-site and upcycling of discarded shipping containers - Francesca Scalisi; Cesare Sposito (Agathón)
The Earth is in a vulnerable state that most scholars attribute to a model of infinite growth on a planet with limited resources. Taking into account this critical environmental context, the paper wants to stimulate new practices for the building industry by suggesting a systemic vision that simultaneously uses multiple sustainable and circular approaches and allows eliminating scraps and waste, by combining traditional and innovative techniques and technologies. In particular, the article shows the potential of off-site in reducing environmental direct and indirect impacts compared to an equivalent conventional construction and recent research on the upcycling of discarded sea containers: they are used as a good practice to enhance an industrial end-of-life product (therefore considered a waste) by re-inserting it into a ‘circular’ economy with a different use than its original one, through non-destructive recycling and, at the same time, improving its value, quality and performance.